Geospatial technology based shoreline change analysis (1992–2022) and predictive forecast modeling for 2032 and 2042, utilizing DSAS, along the eastern coast of India - Harikrishna S.; Gurugnanam B.; Bairavi S. (Kuwait Journal of Science)
This study presents a comprehensive analysis of shoreline dynamics in the Thanjavur district, focusing on erosion and accretion trends from 1992 to 2022. The coastal region was partitioned based on Taluk boundaries to discern distinct patterns in erosion and accretion. The Peravurani region displayed stability, while the Mettupalayam Coast exhibited modest accretion, influenced by sediment deposition from the Tedakkiar River. Mettupalayam had the highest net shoreline movement (NSM), contrasting with the Mandiripattinam coast's prevalent erosion trend. Areas such as Ammani Chattram and Setubava Chattram coast remained relatively stable, while Ganeshapuram, Sendalapattinam, and Sembalpattinam coasts experienced low accretion linked to the Ambuliar River. The study found that the maximum erosion in the study area is 4.1 m/yr (end point rate (EPR)) and 4.21 m/yr (linear regression rate (LRR)) at the Maravakkadu coastal region, and the maximum accretion is 3.75 m/yr (EPR) and LRR of 4.12 m/yr at the Mettupalayam coast. Employing the Kalman filter, future shoreline projections for 2032 and 2042 revealed heightened erosion and accretion trends, identifying vulnerable areas and distinct accretion patterns. It has been predicted that the eastern part of the coastal stretch erodes towards the land, and the western part is accreting. The dynamic interaction of erosion and accretion in Sendalapattinam underscored historical influences on future projections. However, ongoing erosion on the Maravakkadu coast may entail potential economic consequences. The findings emphasize the need for informed coastal management strategies, integrating historical data and future predictions. This will help maintain the coastal ecosystem and community resilience in the changing shoreline dynamics. © 2024